Wuthering Heights - Emily Bronte (London, United Kingdom Usborne Publishing Ltd, 2006)
This volume is a simple, accessible retelling of the great literary classic 'Wuthering Heights', which remains faithful to the original text in it's treatment of the story.
Keywords: Relationships -- Relationships; Romance -- Romance